Characterization and profiling of cell wall lipids from ganoderma boninense-infected oil palm roots - Arnnyitte Alexander (2018)
Basal stem rot disease (BSR) is the most devastating fungal disease in oil palm (OP) caused by Ganoderma boninense, and is one of the most commercially catastrophic diseases in Southeast Asia. This disease has resulted significant decreases in OP yield. On the basis of the importance of early detection for controlling the BSR disease, studies on the mechanism of interaction between OP and G. boninense through metabolomic approaches is currently still on-going. Information on response of OP to BSR is still scarce, particularly concerning changes in the plant membrane-cell wall continuum as the ultimate consequence of biological systems to pathogenesis responses. This interconnection borders most likely a reservoir in signal transduction, defense and antimicrobial metabolites, involving lipids and its derivatives released during the pathogen attack. Therefore this study focuses on lipid components in oil palm roots cell wall towards understanding the pathogenesis and defense response mechanism involved during the OP-G. boninense interaction. In this study, eight-months old OP seedlings were artificially inoculated with G. boninense using rubber wood blocks. Establishment of G. boninense infection was accessed after three and six-months post inoculation referred as first (T1) and second interval (T2), respectively. The cell wall preparation with the highest degree of cytosol component release was produced by lyophilization with homogenization for both OP roots and G. boninense mycelium. The optimum condition on extraction of lipid from cell wall components was investigated using Central Composite Design (CCD). A high lipid extraction yield (3.36%) was obtained under the following extraction conditions: 10 mL of solvent mixture (chloroform: methanol (2:1, v/v)) per gram tissue for 120 min with gentle agitation at 30˚C of extraction temperature. The changes of cell wall-lipid profiles in infected OP (IN) against healthy root in healthy OP (H), at T1 and T2 were investigated via High Performance-Thin Layer Chromatography (HP-TLC) and Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Statistical analysis including Principal Components Analysis (PCA), Partial Least Square-Discriminant Analysis (PLS-DA) and metabolic pathway analysis were performed using Metaboanalyst. The study observed that glycerolipid, linoleic acid, pyruvate and glycerophospholipid metabolism and glycolysis or gluconeogenesis are the most perturbed pathways at T1. Meanwhile, pyruvate metabolism and glycolysis or gluconeogenesis pathways are the most perturbed at T2. Global metabolite pathways found steroid biosynthesis, pyruvate metabolism and glycolysis or gluconeogenesis are the most perturbed pathways in both T1 and T2. There are many lipid metabolites in the OP cell wall are significantly differentially regulated during G. boninense -infection. Using a statistical biomarker validation analysis, PC(6:0/0:0), PC(2:0/2:0), methyl (6E,9E,12E)-6,9,12-octadecatrienoate, PA(18:4(6Z,(Z,12Z,15Z)/0:0), methyl palmitoleate, PA(14:0/ 0:0), γ-linolenic acid and stigmasterol were the metabolites found to be most useful in discriminating infected OP from healthy OP. The results distinguished metabolites present and correspond with G. boninense infection are crossed-reference with the pathogen cell wall-lipid profiles to identify biomarker of the pathogen presence. Ergosterol, 5- lanost-8-en-3-ol, methyl tridecanoate and methyl 9-eicosenoate could be exploited as biomarkers for G. boninense presence. The identified biomarkers may serve as potential biomarkers for G. boninense- infection and assist in the early diagnosis and preventive treatment of BSR disease. The related pathways provide novel insights into developing strategies for better BSR management and resistant OP breed in the future.